Kontrol Diri dan Kecanduan Game Online, serta Hubungannya dengan Perilaku Agresif - Rina Uswatul Khasanah (Universitas Muria Kudus, 2023)
This study aims to determine the relationship between self-control and addiction to online games with aggressive behavior. The instruments used are the self-control scale, the online game addiction scale, and the valid and reliable scale of aggressive behavior. The results showed that there was a relationship between self-control and aggressive behavior in junior high school students, with a significance (0.042 0.05); there was no relationship between online game addiction and aggressive behavior in junior high school students, with a significance (0.619 0.05); there was a relationship between self-control and online game addiction and aggressive behavior in junior high school students, with significance (0.042 0.05). The final study concluded that there was a significant relationship between self-control and addiction to online games with aggressive behavior in junior high school students.